The Merit System’s Adaptation to the Implementation of Bureaucratic Official Recruitment and Promotion Policy in South Central Timor Regency - Severinus Mau; A.G. Subarsono; Yuyun Purbokusumo (Indonesian Association for Public Administration, 2020)
The inequality of human resource (HR) capacity among bureaucrats is an immense challenge confronted by the South Central Timor (SCT) regional government concerning the policy for recruiting and promoting bureaucratic positions. The strong ecological characteristics of the local community with its diverse and varying social, cultural, geographical, economic, and educational environments, coupled with salience of kinship and affiliation have set the backdrop for differences in the bureaucratic personnel’s capacity and performance. Such conditions make it difficult for regional bureaucracies to avoid the emergence of HR capacity disparity issues among bureaucrats. The current study aims to identify and analyze the implementation of bureaucratic position promotion and recruitment policy in SCT Regency. The post-positivist approach was employed in the research by using the descriptive qualitative method. Data were collected through observations, literature study, document study, and in-depth interviews to obtain information, perspectives, and opinions from relevant sources. By comparing theoretical and empirical models, and using the construction of cultural and structural approach models, study results indicate that the merit system’s adaptation developed in recruiting and promoting SCT Regency’s bureaucratic officials tends to use rational representation. This means ethnic representation and native son priority are accommodated in the policy for recruiting and promoting SCT government officials as a manifestation of an achieved mutual consensus, although the process must be conducted through a professional system based on qualifications, competence, and institutional needs.